2021
DOI: 10.3390/molecules26195792
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Mechanisms of Elemene in Reversing Drug Resistance in Tumor Cells: A Review

Abstract: Malignant tumors are life-threatening, and chemotherapy is one of the common treatment methods. However, there are often many factors that contribute to the failure of chemotherapy. The multidrug resistance of cancer cells during chemotherapy has been reported, since tumor cells’ sensitivity decreases over time. To overcome these problems, extensive studies have been conducted to reverse drug resistance in tumor cells. Elemene, an extract of the natural drug Curcuma wenyujin, has been found to reverse drug res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 105 publications
(158 reference statements)
0
9
0
Order By: Relevance
“…Tumor cells can also transfer drug efflux pumps to promote drug resistance. P-Glycoprotein 80 , MDR-1 81 , and ATP-binding cassette subfamily B member 1 8 are drug efflux pumps that transmit multidrug resistance in prostate cancer, OC, leukemia, and osteosarcoma. The capacity of exosomes to transmit multidrug resistance from an adriamycin-resistant variant of MCF-7 to an adriamycin-sensitive variant of MCF-7 was achieved by controlling P-glycoprotein expression 82 .…”
Section: The Effect Of Exosomal Protein Cargo On Cancer Biologymentioning
confidence: 99%
“…Tumor cells can also transfer drug efflux pumps to promote drug resistance. P-Glycoprotein 80 , MDR-1 81 , and ATP-binding cassette subfamily B member 1 8 are drug efflux pumps that transmit multidrug resistance in prostate cancer, OC, leukemia, and osteosarcoma. The capacity of exosomes to transmit multidrug resistance from an adriamycin-resistant variant of MCF-7 to an adriamycin-sensitive variant of MCF-7 was achieved by controlling P-glycoprotein expression 82 .…”
Section: The Effect Of Exosomal Protein Cargo On Cancer Biologymentioning
confidence: 99%
“…The fact that multiple factors affect the activity and expression of these transporters adds further importance to the research in this field. Modulators of P-gp activity and expression include nutritional factors such as salt intake [ 9 , 11 ], patient factors and genetic makeup [ 2 , 31 ], and the activation of various signaling pathways in cancer compared with normal cells [ 5 , 10 , 32 ]. Thus, with the help of current knowledge on the detailed domain structure of P-gp [ 15 , 17 ] and advanced in silico screening technologies [ 6 , 29 ], the search for better P-gp inhibitors shall continue to increase anticancer therapeutic efficacy and decrease patient suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that β-ELE influences exosome content, affects the expression of certain MDR-related miRNAs, and reduces the exosome-mediated transmission of drug resistance, thereby enhancing the cells’ capacity to overcome MDR ( Zhang J. et al, 2015 ). In the exosomes of multidrug-resistant gastric cancer cells, miR-1323 is significantly expressed, which encourages EMT of gastric cancer sensitive cells and enhances their capacity for invasion and migration ( Tan et al, 2021 ). The expression of Cbl-b is likewise suppressed by miR-1323, resulting in the attenuation of drug resistance in cancer cells with MDR.…”
Section: Natural Product—derived Compounds Overcome Cancer Drug Resis...mentioning
confidence: 99%